Uranium and lithium extraction from seawater: challenges and opportunities for a sustainable energy future - Lim, Yu Jie (2024)
Amid the global call for decarbonization efforts, uranium and lithium are two important metal resources critical for securing a sustainable energy future. Extraction of uranium and lithium from seawater has gained broad interest in recent years due to the thousand-fold higher quantity available as compared to land-based reserves, but the challenge lies in the ability to extract them at ultralow concentrations. Over the past two decades, the rise of nanotechnology has brought together an abundance of adsorptive materials that are poised to incentivize technologies capable of achieving high extraction performances. The objective of this review is to consolidate recent advances in uranium and lithium extraction from the standpoint of adsorptive materials and technologies for application in seawater. First, adsorptive materials for uranium extraction are reviewed, before we discuss the technology platforms into which they can be deployed (e.g., membrane-based adsorption). Second, a comprehensive review of lithium extraction technologies is presented by examining the materials and platforms capable of achieving high extraction performances. Since the scope of this review is geared towards application in seawater and desalination brines (in particular, seawater reverse osmosis (SWRO) brine), we highlight the main challenges to date – selectivity required against competing ions and long-term stability against marine biofouling. Then, we put together an outlook, featuring our perspectives on next-generation materials and techno-economic analysis. Since the properties of desalination brines are unique from those of seawater, we also distinguish the traits of next-generation materials to be used for SWRO brines to provide insights for advancing new tailored materials and technologies for application in the latter. Overall, this review sums up state-of-the-art technologies for uranium and lithium extraction, putting into perspective various technology platforms to realize high extraction performances that can address our future demands for uranium and lithium at the water-energy nexus.